Readability Analysis of Rancagé Diajar Basa Sunda for Junior High Schools: Evidence from the Fry Graph - Tanti Sri Wahyuni; Nunuy Nurjanah; Haris Santosa Nugraha (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the readability level of 43 texts in the book Rancagé Diajar Basa Sunda for junior high school students using Fry Graphs, as well as to evaluate their suitability for readers aged 12 to 15 years. This study uses a document analysis method comprising steps such as text identification, calculation of sentence and syllable counts, graph mapping, and interpretation of results in the context of Sundanese. The results showed that only 11 texts (26%) were in the "suitable" category, while most were in the low and very low categories. However, such low scores do not necessarily reflect incompatibility, because the clarity of sentence structure is a way to accommodate the limitations in mastery of Sundanese cultural vocabulary among junior high school students. The results of this study show that Fry's Graph must be interpreted in a real way in Sundanese. By implication, teachers and book writers must balance simple sentences with important cultural vocabulary. At the same time, authorities can use these results to formulate readability standards for local Sundanese materials.